Research on Key Technologies of Heterogeneous Wireless Network Resource Management Based on Centralized Radio Access Network Architecture - Lin Tian; Guowei Zhai; Liang Huang; Yiqing Zhou; Jinglin Shi (Dianxin kexue)
The future broadband wireless communication network will be a heterogeneous network with multiple access technologies seamlessly integrated. In such heterogeneous network, the key issues are how to share resources such as frequency, software, hardware and so on among different types of networks to reduce cost as well as to provide better services to users. Therefore, a heterogeneous network resource convergence platform was proposed based on the centralized radio access network architecture. This platform provides a feasible solution to support resource cooperation among different networks. Moreover, the key technologies were illustrated in detail, such as resource virtualization, processing resource allocation, dynamic frequency share, network coverage optimization, system performance analysis, etc.